IMPLEMENTATION OF REGIONAL MARKETREGULATION OF THE DIRECTOR COMPANY LAMONGAN DISTRICTNUMBER 150 2014 TECHNICAL GUIDELINES ON HANDLINGLAMONGAN NEW MARKET IN THE MARKET - AFIF ZULISANTO (Universitas Negeri Surabaya, 2016)
Regional Director of Market Regulation Lamongan No. 150 of 2014 on Technical Guidelinesfor Management of Market in Lamongan one market is in New Market. Implementation is significantin improving the service management market is still found problems that occur in the field, includinghygiene in the New Market Lamongan is still quite alarming , there's also garbage strewn in the market. Moreover , at some point the market is also still found a broken ceramic flooring market , leaky roofsand tiles so it is quite disturbing activities of traders in the rainy season . This study aimed to describethe implementation of the Regional Implementation Director of Market Regulation Lamongan No. 1502014 About the Technical Guidelines for Management Market In New Market Lamongan.This type of research is a descriptive study . By using qualitative research methods , while thefocus of the study is variable , namely the implementation of the communication , resources,disposition and bureaucratic structure . Researchers at the New Market location Lamongan .Informants consisted of PD Pasar , traders and buyers . Data validity checking techniques usingtriangulation . Data collection techniques are observation, interviews and documentation . Dataanalysis techniques to study arranged systematically with data reduction , data presentation , drawingconclusions.The results showed that views on the communication variables still found problems related tolack of socialization by PD Pasar to the merchant. Then linked variable disposition still foundproblems related to double job market between PD officers. Associated variable resource still foundobstacles from the standpoint of market facilities which are now increasingly broken and notmaintained as well as the variable structure of the bureaucracy of the executive in the bureaucraticstructure of PD Pasar already perform the duties and functions of each, so expect the implementers cantake into account every variable implementation ie related communication, bureaucratic structure,resources, and disposition. In order for the implementation of the Implementation Regulation of theDirector of PD Pasar Lamongan District Number 15 Year 2014 About the Technical Guidelines forHandling Market in New Market Lamongan can run well by improving market facilities, meetregularly to socialize, and the policy implementers perform their duties and obligations in accordancewith the objectives has been established.Keywords: Implementation, Management Market